Incentive-linked prescribing and the plights of patients: a qualitative study in Pakistan - Muhammad Naveed Noor; Zahida Azizullah; Haider Safdar Abbasi; Nina van der Mark; Afifah Rahman-Shepherd; Amna Rehana Siddiqui; Mishal Sameer Khan; Rumina Hasan; Sadia Shakoor (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the perceived impact of incentive-linked prescribing (ILP) on the everyday lives of patients in Pakistan. Methods: Adopting a qualitative approach, in-depth interviews were conducted with 26 patients in Karachi. A convenient sampling method was used to recruit patients from different pharmacies located in all six districts of Karachi namely East, West, South, Central, Korangi, and Malir. The interviews were thematically analyzed using the software NVivo Version.12. Results: ILP was perceived to affect patients in three interrelated ways: financial difficulty, mental distress, and difficulty in adhering to medical treatments. Most of the participants reported experiencing financial difficulties and were unable to afford everyday household needs. ILP was believed to make physicians prescribe expensive brands, which in turn, added to patients’ financial difficulties. Due to expensive medications, some patients stopped seeking healthcare from physicians and instead relied on home remedies. ILP-related financial burden on patients was also perceived to be a contributor to their mental distress. Conclusion: Patients are increasingly becoming aware of physicians’ engagement in ILP, and believe it harms them in different ways. It has important implications for physicians’ reputations in society. Physicians must adhere to the principles of patient-centred care by avoiding ILP. Keywords: Incentives, physicians, patients, pharmaceutical companies, healthcare, patient-centered care, Pakistan